Hospitalization trends of the Inflammatory Bowel Disease landscape: A nationwide overview of 16 years. Issue 7 (July 2019) - Dias, Cláudia Camila; Santiago, Mafalda; Correia, Luís; Portela, Francisco; Ministro, Paula; Lago, Paula; Trindade, Eunice; Freitas, Alberto; Magro, Fernando; ,
Abstract: Introduction: In this study, we aimed to determine the hospitalization rates of Inflammatory Bowel Disease (IBD) in a southern-european country and its associated charges over a period of 16 years. Methods: We identified all discharges with a primary diagnosis of Crohn's disease (CD) or ulcerative colitis (UC) between 2000 and 2015 in data provided by the Central Administration of Health Services (ACSS). National estimates of hospitalization rates were assessed and adjusted to gender, age, population, and hospitalizations. Hospitalization charges were also assessed. Results: There were an estimated 31 358 and 16 669 discharges for CD and UC, respectively. From 2000 to 2015, hospitalization rates per 100000 habitants increased for CD (8.4–11.2) and remained stable for UC (4.4–4.9). The hospitalization rate for IBD increased slightly over time (12.8 per 100 000 habitants in 2000 and 16.1 in 2015). Annual total hospitalization charges amounted to 4.0M€ in 2000 and 5.7M€ in 2015. This increase was mainly due to a rise in the total expenses of CD-related hospitalizations. Conclusion: CD hospitalization rates per 100000 inhabitants increased over time while remaining constant for UC. Hospitalization charges for IBD increased approximately 2.0M€ during the study period, representing an important burden in the national healthcare system.